Description and Critical Evaluation of Models of Psychology Practice in the Pediatric Intensive Care Unit - (:unkn) unknown (My University, 2024)
During and after hospitalization in the pediatric intensive care unit (PICU), a significant proportion of patients and their family members experience clinical levels of distress (i.e., traumatic stress, anxiety, and depression). Pediatric psychologists are well-suited to support families during hospitalization and are increasingly present in PICUs. Models of psychology practice have been explored in other pediatric settings, but a comprehensive assessment of models of psychology practice in the PICU has not been conducted. The present study aimed to evaluate current models of psychology practice in PICUs and explore psychologists’ perceptions of the ideal model of care for PICU families. Fourteen participants (13 psychologists, 1 psychology intern; 100% White, 93% female) with recent PICU experience and representing 13 institutions completed a survey and participated in one of five focus groups regarding their institution’s current model of psychology practice and recommendations for the ideal model. The most common institutional model of psychology practice was a hybrid model involving both service-specific psychologists (i.e., psychologists dedicated to a specific pediatric population who see their patients when they are in the PICU) as well as consultation-liaison psychologists (i.e., psychologists who serve multiple inpatient units and are referred to cases in the PICU). Psychologists embedded in the PICU were less common. Participants described that having dedicated PICU time would be ideal and offer several benefits (e.g., improved identification of patients and families). These findings contribute to better understanding of current models of psychology practice and offer preliminary suggestions for an improved model that requires further investigation. Advocacy strategies such as collecting and utilizing outcomes data, sharing information about the role of psychology, establishing standards of care, fostering relationships, and being present in the PICU will support the recommended improvements.
Keywords: Critical Care; Models; Pediatric; Pediatric Intensive Care Unit; PICU; Psychology